Transcriptome Analysis to Identify the Putative Biosynthesis and Transport Genes Associated with the Medicinal Components of Achyranthes bidentata Bl. - Li, Jinting; Wang, Can; Han, Xueping; Qi, Wanzhen; Chen, Yanqiong; Wang, Taixia; Zheng, Yi; Zhao, Xiting (Frontiers in Plant Science, 2016)
Achyranthes bidentata is a popular perennial medicine herb used for thousands of years in China to treat various diseases. Although this herb has multiple pharmaceutical purposes in China, no transcriptomic information has been reported for this species. In addition, the understanding of several key pathways and enzymes involved in the biosynthesis of oleanolic acid and ecdysterone, two pharmacologically active classes of metabolites and major chemical constituents of A. bidentata root extracts, is limited. The aim of the present study was to characterize the transcriptome profile of the roots and leaves of A. bidentata to uncover the biosynthetic and transport mechanisms of the active components. In this study, we identified 100,987 transcripts, with an average length of 973.64 base pairs. A total of 31,634 (31.33%) unigenes were annotated, and 12,762 unigenes were mapped to 303 pathways according to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database. Moreover, we identified a total of 260 oleanolic acid and ecdysterone genes encoding biosynthetic enzymes. Furthermore, the key enzymes involved in the oleanolic acid and ecdysterone synthesis pathways were analyzed using quantitative real-time polymerase chain reaction (qRT-PCR), revealing that the roots expressed these enzymes to a greater extent than the leaves. In addition, we identified 85 ATP-binding cassette (ABC) transporters, some of which might be involved in the translocation of secondary metabolites.